Analisis Percepatan Pelaksanaan Pekerjaan pada Proyek Pembangunan Safety Riding Centre - Siregar, Dorlan (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 2 (2024)DO - 10.24843/PJIIB.2024.v24.i02.p03, 2024)
The Accelerating project completion must be done with proper planning. One of the alternatives that can be used to support the acceleration of work activities is by adding manpower and working hours, in order to address delays in a project. To achieve maximum benefits without compromising workplace safety and job quality. The aim of this research is to analyze the acceleration of the implementation of the safety riding center project by adding optimal manpower and working hours. The method used in this research is a descriptive method with a case study approach. The Crashing method is used to expedite the delay in the riding center project using Microsoft Office Project 2016 as a data processing tool. After analyzing the data, it can be concluded that there are 3 critical paths that affect the implementation of the safety riding center project, and adding optimal manpower and working hours is performed. The results obtained after the analysis show that the upper structure work has the longest critical path with an initial completion time of 161 days, which is accelerated by 38 days to become 123 days earlier with the addition of 8 workers. With an initial cost of 4,519,890,373 becoming 4,519,965,373. The higher the cost incurred, the faster the delayed work is completed.